Systematic review with meta‐analysis: the prevalence of post‐colonoscopy colorectal cancers using the World Endoscopy Organization nomenclature. Issue 10 (29th September 2021) - Kang, James H.‐E.; Evans, Nicole; Singh, Siddharth; Samadder, Niloy J.; Lee, Jeffrey K.
Summary: Introduction: Post‐colonoscopy colorectal cancers (PCCRCs) have been proposed as a performance metric for colonoscopy quality assurance programs. Previously, there was no standardised terminology or reporting methods. In 2018, the World Endoscopy Organization (WEO) advised standardised definitions and prevalence calculation methodology. Aims: To assess PCCRC burden using WEO standardised methods, to explore causes of heterogeneity, and to review changes in prevalence over time Methods: We updated a prior systematic review by searching Ovid MEDLINE and EMBASE databases from 1 January 2013 to 31 January 2021 to identify population‐based studies (or multicentre studies representative of the local population) reporting PCCRC prevalence (PROSPERO [CRD42020183796]). Two authors independently determined study eligibility, assessed quality, and extracted data. We estimated the PCCRC 3‐year prevalence using WEO‐recommended methodologies and investigated between‐study sources of heterogeneity. We examined changes in prevalence over time. Results: Fifteen studies reporting on 25 872 PCCRC cases met eligibility criteria. Pooled PCCRC 3 year prevalence was 8.2% (95% CI = 6.9%‐9.4%, I 2 = 98.2%) across four European studies using WEO precise methodology. Proximal PCCRC prevalence was greater than distal (9.7% [95% CI = 7.0%‐12.4%] vs 5.4% [95% CI = 2.9%‐7.8%], I 2 = 99.2%). Seven studies reporting PCCRC rates over time showed no consistent trend: four showed a decrease, one an increase and two were unchanged. Between‐study heterogeneity was high. Conclusions: Pooled 3‐year PCCRC prevalence was 8.2% (95% CI = 6.9%‐9.4%). Despite WEO standardised methodology to define and calculate PCCRC rates, there was significant heterogeneity among studies. Comparing rates between populations remains challenging and additional studies are needed to better understand the global PCCRC burden to inform quality assurance programs. Abstract : Four studies used WEO endorsed nomenclature and methods to define PCCRC prevalence. Between‐study heterogeneity was high, suggesting that consistent methods for determining PCCRC prevalence are necessary but may not be sufficient for benchmarking. Additional population‐based studies using standardised nomenclature from different countries are required to more accurately assess the global burden of PCCRC.